2023
DOI: 10.3390/cancers15205016
|View full text |Cite
|
Sign up to set email alerts
|

Internet of Things-Assisted Smart Skin Cancer Detection Using Metaheuristics with Deep Learning Model

Marwa Obayya,
Munya A. Arasi,
Nabil Sharaf Almalki
et al.

Abstract: Internet of Things (IoT)-assisted skin cancer recognition integrates several connected devices and sensors for supporting the primary analysis and monitoring of skin conditions. A preliminary analysis of skin cancer images is extremely difficult because of factors such as distinct sizes and shapes of lesions, differences in color illumination, and light reflections on the skin surface. In recent times, IoT-based skin cancer recognition utilizing deep learning (DL) has been used for enhancing the early analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…For example, Dahou et al [5] presented an alternative skin cancer detection method and achieved excellent performance across multiple datasets. Obayya et al [6] proposed an automated skin cancer classification and detection model utilizing ODL-SCDC technology, which extends the application scope to the Internet of Things (IoT) environment. Gulshan et al [7] demonstrated the clinical potential of using deep learning algorithms for the automatic detection of diabetic retinopathy.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Dahou et al [5] presented an alternative skin cancer detection method and achieved excellent performance across multiple datasets. Obayya et al [6] proposed an automated skin cancer classification and detection model utilizing ODL-SCDC technology, which extends the application scope to the Internet of Things (IoT) environment. Gulshan et al [7] demonstrated the clinical potential of using deep learning algorithms for the automatic detection of diabetic retinopathy.…”
Section: Related Workmentioning
confidence: 99%